2008
DOI: 10.3988/jcn.2008.4.3.99
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effects of Antiepileptic Drugs

Abstract: Antiepileptic drugs (AEDs) can adversely affect cognitive function by suppressing neuronal excitability or enhancing inhibitory neurotransmission. The main cognitive effects of AEDs are impaired attention, vigilance, and psychomotor speed, but secondary effects can manifest on other cognitive functions. Although the long-term use of AEDs can obviously elicit cognitive dysfunction in epilepsy patients, their cognitive effects over short periods of up to a year are inconclusive due to methodological problems. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
3
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(138 citation statements)
references
References 59 publications
(57 reference statements)
4
119
3
12
Order By: Relevance
“…Furthermore, clinically significant adverse cognitive effects have been described in association with the use of topiramate, including memory deficit, language problems and impaired attention, vigilance, and psychomotor speed (Park and Kwon, 2008). These effects are dosage-dependent and become prominent for doses higher than 75 mg/day (Park and Kwon, 2008). However, when titrated slowly, doses of 300 mg/day were tolerated by most patients.…”
Section: Topiramatementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, clinically significant adverse cognitive effects have been described in association with the use of topiramate, including memory deficit, language problems and impaired attention, vigilance, and psychomotor speed (Park and Kwon, 2008). These effects are dosage-dependent and become prominent for doses higher than 75 mg/day (Park and Kwon, 2008). However, when titrated slowly, doses of 300 mg/day were tolerated by most patients.…”
Section: Topiramatementioning
confidence: 99%
“…For example, the US FDA recently changed topiramate's pregnancy classification to category D, based on new data reviewed by the North American Drug Pregnancy Registry showing an increased risk of oral clefts in infants exposed to topiramate as a single therapy for epilepsy in the first trimester of pregnancy (Medwatch, 2011). Furthermore, clinically significant adverse cognitive effects have been described in association with the use of topiramate, including memory deficit, language problems and impaired attention, vigilance, and psychomotor speed (Park and Kwon, 2008). These effects are dosage-dependent and become prominent for doses higher than 75 mg/day (Park and Kwon, 2008).…”
Section: Topiramatementioning
confidence: 99%
“…As a rule, treatment with AEDs in elderly patients combines the described challenges of drug-drug interactions and cardiovascular risk with age-related changes in pharmacokinetics and increased susceptibility to cognitive side effects in particular [Siniscalchi, 2012]. Regarding cognitive function, LTG, LEV, and GBP seem to have fewer adverse cognitive effects than CBZ [Park, 2008].…”
Section: Aed Treatmentmentioning
confidence: 99%
“…In previous studies, high doses of TPM and LTG have been reported to be associated with brain maturation defects including cognitive impairments in some offspring of TPM-or LTG-treated mothers [3]. Impairments in cognitive functions such as learning and memory have usually been associated with congenitally occurring structural and molecular alterations in the limbic system, particularly the hippocampus of offspring [4].…”
Section: Discussionmentioning
confidence: 99%